Chloride Induced Corrosion Behaviour Of Mild Steel Rebars: A Case Study Of Calcined Clay Pozzolan Containing Concrete - Damoah, L.N.W.; Akoto, R.N.A.; Mussey, B.K.; Bensah, Y.D. (Scientific African, 2025)
The partial replacement of 5 – 30 % by mass of ordinary Portland cement with clay pozzolana in concrete, gives impressive chemical characteristics to the resulting material. Corrosion behavior of reinforcement steel in two types of concrete mixtures: Ordinary Portland Cement (OPC) containing concrete and 30 % clay pozzolana cement (PPC) containing concrete are studied. These concretes were exposed to 3 % and 5 % (w/v) solutions of NaCl as corrosion acceleration media. Electrochemical polarization measurements were performed for 3, 7, 15, and 23 days. The corrosion rate obtained from the polarization curves revealed that samples exposed to 5 %(w/v) NaCl had higher corrosion rates than those exposed to 3 %(w/v) NaCl. The addition of 30 % clay pozzolan as a partial replacement for OPC in concrete resulted in an average reduction in the corrosion rate of approximately 90 % in 3 %(w/v) NaCl and 74 % in 5 %(w/v) NaCl over 23 days.
Research Article
Keywords: Clay Pozzolan Cement; Corrosion currents; Portland cement; Reinforced concrete; Steel corrosion; Tafel plots